EXPERIMENTAL-MORPHOLOGICAL SUBSTANTIATION OF MICROSURGICAL INVAGINATION ESOPHAGO-GASTRIC ANASTOMOSES - P. V. Samoylov (Креативная хирургия и онкология)
New ways of formation of microsurgical invagination late-side and end-terminal esophago-gastric anastomoses in the resection of the esophagus and cardia stomach are proposed in the experiment on animals. Objects of the experiment are 24 purebred dogs. Experimental approbation of microsurgical invagination PGA demonstrated the feasibility, reliability and high functionality of ways. The microsurgical techniques, single row of continuous seam without capture mucosa when creating anastomoses, allows to improve the immediate and distant results of operations. Anastomoses have high antireflux properties that due to constructive features, due to the inclusion in the anastomosis zone of duplikatory of alternate layers of muscles of the esophagus and stomach, forming an artificial sphincter, which is confirmed by the functional and morphological methods of research.